Center of Islamic Library: The Gateway to Increasing Islamic Literacy - Iswanda Fauzan S (Universiti Sains Islam Malaysia, 2024)
The role of mosque library in wide-spreading and engraft Moslem's teaching is very strategic. Most of major and important library in the past like Baitul Hikmah in Baghdad, Ibn Suwar's library in Basrah, Darul Hikmah in Kairo, represent the message that the intelligence o f Moslems in the time, is directly proportional with the quality of its information institute, in this context, the library itself The Indonesian Islamic Library Center (PPII) is an information institute, which is become the center of Islamic literation in Indonesia and to be under,for 643.843 library mosques. The aim of this study is to understand the purpose of the PPII itself for wide-spreading and developing the Islamic literation in Indonesia such as books, magazines, journals, reports, and online portals. The design used for this study is descriptive-longitudinal. The collectable data including the history of PPII, services and literation works, also the development of Indonesian literation from 19 70 until 201 0. The result shows that the existence of PPII improving the quality and quantity of Islamic literarion in Indonesia. PPII is also become the public representation,for Islamic literation development in Indonesia.